Impact of childhood maltreatment on psychosomatic outcomes among men and women with disabilities. Issue 24 (20th November 2022) - Pebole, Michelle M.; Greco, Chelsea E.; Gobin, Robyn L.; Phillips, Brian N.; Strauser, David R.
Abstract: Purpose: This project examined the impact of childhood maltreatment types on psychosomatic outcomes among adults with a range of self-reported disabilities. Materials and methods: Participants ( n = 643) were recruited using Amazon Mechanical Turk and Cloud Research. Single-item questions assessed sociodemographic information. The Childhood Trauma Questionnaire measured childhood maltreatment types (emotional, physical, and sexual abuse, and emotional and physical neglect) and the RAND-36 Item Health Survey evaluated physical functioning, pain, and energy/fatigue. Logistic regressions determined associations between childhood trauma and psychosomatic outcomes; stratified models compared men and women. Results: Multivariate-adjusted models indicated physical abuse was positively associated with poor physical functioning (OR: 2.03; 95%CI: 1.35–3.06) with this relationship being stronger for men (OR: 3.25; 95%CI: 1.42–7.43) than women (OR: 1.91; 95%CI: 1.17–3.13). Adjusted models showed that physical neglect was protective against fatigue (OR: 0.58; 95% CI: 0.36–0.94), while emotional neglect increased the risk of fatigue (OR: 1.74; 95%CI: 1.02–2.95). Lastly, physical abuse was positively associated with pain (OR: 1.53; 95%CI: 1.01–2.33). This relationship was stronger in men (OR: 4.99; 95%CI: 1.91–12.99). Conclusions: Results improve our understanding of risk factors for poor physical health outcomes and can guide the development of trauma-sensitive rehabilitation services. Implications for Rehabilitation: Individuals with disabilities who report childhood maltreatment may experience poor psychosomatic outcomes in adulthood. Consequences of experiencing childhood maltreatment may manifest differently between men and women over the course of the lifespan. It is essential to integrate trauma-informed principles into treatment plans for individuals with poor psychosomatic health. Rehabilitation professionals should screen for abuse and refer individuals to the appropriate mental and physical health services.